IMPLEMENTASI PEDOMAN PEMBERITAAN MEDIA SIBER PADA BERITA KEKERASAN SEKSUAL DI MEDIA SIBER GORIAU.COM - Yunanda, Sigit Eka; Yesicha, Chelsy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
A true news is a construction carried out by the media, and according to Gregg Barak in the theory of newsmaking criminology the construction of a violent news is often exploited because psychologically humans are interested in begging for others. Therefore the news of violence that is presented by moving emotions is very popular in the community. The more emotional and dramatic a news of violence, the more it will inspire people to click on the news. However, there is no indication of the exploitation of reporting in the theory of newsmaking criminology, so that to measure the quality of reporting, technical rules related to reporting include one of the Guidelines for Media News Coverage.This research uses Newsmaking Criminology by Gregg Barak by using quantitative content analysis methods with a descriptive approach. The research subjects, namely the news narrative contained by GoRiau.com.com, from 1 April to 31 July 2019 totaled 21 news. This research is intended to describe the Implementation of Guidelines for Media News Coverage conducted by Goriau.com regarding sexual violence. Data obtained by coding performed by 3 coder.Based on the results of the study it can be seen that the implementation of the Guidelines for Media News Coverage associated with reporting sexual violence by GoRiau.com is generally quite good. From the Four Indicators examined, it is seen that as a whole 75% of the total coverage was implemented. However, GoRiau.com still made a number of reporting errors related to the description of victims and the use of euphemisms in describing sexual violencekeyword: sexual harassment, content analysis, cyber media